ROTEM as a Predictor of Mortality in Patients With Severe Trauma - Smith, Alaina R.; Karim, Saleema A.; Reif, Rebecca R.; Beck, William C.; Taylor, John R.; Davis, Benjamin L.; Bhavaraju, Avi V.; Jensen, Hanna K.; Kimbrough, Mary K.; Sexton, Kevin W. (The Journal of surgical research, 2020)
Hemorrhage, especially when complicated by coagulopathy, is the most preventable cause of death in trauma patients. We hypothesized that assessing hemostatic function using rotational thromboelastometry (ROTEM) or conventional coagulation tests can predict the risk of mortality in patients with severe trauma indicated by an injury severity score greater than 15. We retrospectively reviewed trauma patients with an injury severity score >15 who were admitted to the emergency department between November 2015 and August 2017 in a single level I trauma center. Patients with available ROTEM and conventional coagulation data (partial thromboplastin time [PTT], prothrombin time [PT], and international normalized ratio) were included in the study cohort. Logistic regression was performed to assess the relationship between coagulation status and mortality. The study cohort included 301 patients with an average age of 47 y, and 75% of the patients were males. Mortality was 23% (n = 68). Significant predictors of mortality included abnormal APTEM (thromboelastometry (TEM) assay in which fibrinolysis is inhibited by aprotinin (AP) in the reagent) parameters, specifically a low APTEM alpha angle, a high APTEM clot formation time, and a high APTEM clotting time. In addition, an abnormal international normalized ratio significantly predicted mortality, whereas abnormal PT and PTT did not. A low APTEM alpha angle, an elevated APTEM clot formation time, and a high APTEM clotting time significantly predicted mortality, whereas abnormal PT and PTT did not appear to be associated with increased mortality in this patient population. Viscoelastic testing such as ROTEM appears to have indications in the management and stabilization of trauma patients.